Sisters in the struggle : African American women in the civil rights-Black power movement - Collier-Thomas, Bettye; Franklin, V. P. (Vincent P.), 1947- (New York University Press, 2001)
Tells the stories and documents the contributions of African American women involved in the struggle for racial and gender equality through the civil rights and black power movements in the United States.